Investigating Muslim non-consumers’ intention to use Islamic bank: perceived social value (PSV) and awareness - Ery Dwi Pantari; Hendy Mustiko Aji (Jurnal Siasat Bisnis, 2020)
As a country with the largest Muslim population in the world, Indonesia has a greater market opportunity for Islamic bank than the conventional. When it compares with other Islamic countries, the market share of Islamic banks is still less appealing. This situation is certainly an interesting problem to be researched. The purpose of this study is to examine the influence of subjective norms, awareness, perceived values, attitudes, and intentions to use Islamic banks based on the Theory of Planned Behavior. This study uses quantitative approach where the data is gathered by distributing the online and offline questionnaires. In total, there are 575 respondents collected. This study finds that Muslim non-customers’ intention to use Islamic banks is strongly affected by subjective norms, awareness, and attitudes. It is also found that perceived social value (PSV) does not significantly affect intention to use Islamic banks. This study argues that using Islamic bank is not something ‘special’ to gain social acceptance or positive image in society. It is also supported by the fact that most Muslims in Indonesia do not use Islamic banks.